2000
DOI: 10.1590/s0037-86822000000200005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo clínico da malária falciparum em crianças em Manaus, AM, Brasil

Abstract: Resumo As características clínicas da malária falciparum foram estudadas em 61 crianças com idade de 0 a 14 anos, atendidas em centro de referência em Manaus, entre outubro e dezembro de 1997. Os sintomas encontrados foram febre (98,4%), cefaléia (80,3%), calafrios (68,9%), sudorese (65,6%), mialgia (59%), náuseas (54,1%), lombalgia (49,2%), vômitos (49,2%), tosse (45,9%), artralgia (31,1%), diarréia (34,4%), dispnéia (8,2%), convulsões (8,2%) e tonturas (4,9%). Palidez cutâneo-mucosa e anemia foram observadas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
0
6
0
6
Order By: Relevance
“…Discussão É evidente que fatores genéticos e do envolvimento, bem como a sua interação e covariação, são agentes de forte responsabilidade na explicação da variação nos níveis da aptidão física a nível populacional. A importância dos fatores genéticos nas componentes da aptidão física tem sido estudada em famílias nucleares (BouChard, an, riCe, sKinner, wilMore, GaGnon, pérusse, leon & rao, 1999;BouChard et al, 1998;KatzMarzyK et al, 2001;pérusse, GaGnon, provinCe, rao, wilMore, leon, BouChard & sKinner, 2001;pérusse, lortie, leBlanC, treMBlay, theriault & BouChard, 1987b;pérusse et al, 1987a) gêmeos (Beunen & thoMis, 2000;Beunen, thoMis, peeters, Maes, Claessens & vlietinCK, 2003;Fernandes & Maia, 2006;Maia, lopes & Morais, 2001;Maia et al, 2003;silBerG, Meyer, Maes, hewitt, siMonoFF, piCKles, loeBer & eaves, 1996) e fratrias (vasques, 2005) de populações de países desenvolvidos. No entanto, existe uma escassez de estudos sobre a influência desses fatores na variabilidade fenotípica das componentes da aptidão física em populações de países em transição sociodemogáfica, o que limita a comparação dos resultados do presente estudo com os que estão disponíveis na literatuta conduzindo, necessariamente, a alguma insuficiência explicativa.…”
Section: Resultsunclassified
“…Discussão É evidente que fatores genéticos e do envolvimento, bem como a sua interação e covariação, são agentes de forte responsabilidade na explicação da variação nos níveis da aptidão física a nível populacional. A importância dos fatores genéticos nas componentes da aptidão física tem sido estudada em famílias nucleares (BouChard, an, riCe, sKinner, wilMore, GaGnon, pérusse, leon & rao, 1999;BouChard et al, 1998;KatzMarzyK et al, 2001;pérusse, GaGnon, provinCe, rao, wilMore, leon, BouChard & sKinner, 2001;pérusse, lortie, leBlanC, treMBlay, theriault & BouChard, 1987b;pérusse et al, 1987a) gêmeos (Beunen & thoMis, 2000;Beunen, thoMis, peeters, Maes, Claessens & vlietinCK, 2003;Fernandes & Maia, 2006;Maia, lopes & Morais, 2001;Maia et al, 2003;silBerG, Meyer, Maes, hewitt, siMonoFF, piCKles, loeBer & eaves, 1996) e fratrias (vasques, 2005) de populações de países desenvolvidos. No entanto, existe uma escassez de estudos sobre a influência desses fatores na variabilidade fenotípica das componentes da aptidão física em populações de países em transição sociodemogáfica, o que limita a comparação dos resultados do presente estudo com os que estão disponíveis na literatuta conduzindo, necessariamente, a alguma insuficiência explicativa.…”
Section: Resultsunclassified
“…In contrast, our study did not show reported cases in the Amazonas, Acre, Tocantins, and Pará states, suggesting either successful prevention campaigns, underreported cases, or both. Although malaria prevalence has gradually been declining in Brazil [ 43 , 44 ], we believe that the number of underreported cases in the North region is high, as some studies have described cases in children [ 45 , 46 ] in this area. On the other hand, the spatial distribution of malaria has been found to be heterogeneous in other Brazilian regions.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of dengue in children living in areas in the N Region [141,142], CO Region [145] and SE Region [147] have led to a disruption of routine health services, demanding further efforts towards providing technical training to health professionals working on the frontline of dengue treatment in children's patient care. As for malaria, researches had investigated children and adolescents who live in the N region [151,152]. The lethality was 1.6% and besides the common symptoms of malaria triad (fever, chills and headache) they had among others like pallor, anemia, myalgia, vomiting and some degree of malnourishment [151], and there was a prevalence of malaria among adolescents [152].…”
Section: Grandjean Et Almentioning
confidence: 99%
“…As for malaria, researches had investigated children and adolescents who live in the N region [151,152]. The lethality was 1.6% and besides the common symptoms of malaria triad (fever, chills and headache) they had among others like pallor, anemia, myalgia, vomiting and some degree of malnourishment [151], and there was a prevalence of malaria among adolescents [152].…”
Section: Grandjean Et Almentioning
confidence: 99%